Reporting Emerging Resistance of Streptococcus pneumoniae from India - Chawla, Kiran (Medknow Publications, 2010)
BACKGROUND: There are reports of emergence of resistant strains of S. pneumoniae showing resistance to penicillin from all over the world, and now, resistance to multiple drugs (multidrug-resistant strains) has been added to it. However, scanty reports are available so far from India, depicting such resistance. AIMS: The aim of the present study is to look for the prevalence of penicillin-resistant pneumococci and also the multidrug-resistant strains among S. pneumoniae, isolated from respiratory specimens, in the coastal part of South India. SETTINGS AND DESIGN: A cross-sectional study was conducted from June 2008 to December 2008, in our tertiary care center. Fifty pathogenic clinical isolates were collected from patients suffering from lower respiratory tract infections. MATERIALS AND METHODS: Penicillin resistance was screened by 1 μg oxacillin disk on Muller-Hinton blood agar followed by Minimum Inhibitory Concentration (MIC) detection by the agar dilution method according to the Clinical Laboratory Standards Institute (CLSI) guidelines. Antibiotic susceptibility for other antibiotics was carried out by the Kirby Bauer disk diffusion method followed by an E-test with HiComb test strips from Hi-media. RESULTS: Out of 50 isolates, 4% (95% Confidence Interval - 1.4, 9.4) showed total resistance to penicillin, whereas, 10% (95% CI; 1.6, 18.3) showed intermediate resistance. These penicillin-resistant pneumococci (4%) were also found to be multidrug-resistant (MDR) strains. Maximum resistance was observed for cotrimoxazole and tetracycline (24% each with 95% CI; 12.2, 35.8) followed by erythromycin and ciprofloxacin (14% each with 95%CI; 4.4, 23.6). CONCLUSIONS: Increasing emergence of the resistant strains of S. pneumoniae in the community set up requires continuous monitoring and a restricted use of antibiotics to keep a check on its resistance pattern, for an effective treatment plan.